Crossed responses found in human trapezius muscles are not H‐reflexes. Issue 3 (22nd November 2013) - Vangsgaard, Steffen; Nørgaard, Lars T.; Madeleine, Pascal; Taylor, Janet L.
ABSTRACT Introduction: We sought to confirm the presence of crossed short‐latency reflexes in trapezius. Methods: Mmax and Hmax were measured in the ipsilateral trapezius in 10 subjects by percutaneous electrical stimulation of the accessory nerve and the cervical nerves of C3/4 respectively. Repeated stimulation of the C3/4 cervical nerves was performed during 3 different tasks (relaxation, contraction of ipsilateral side, contraction of contralateral side). Results: Ipsilaterally, responses increased significantly with an increase in the prestimulus electromyogram (EMG) and decreased significantly with a decrease in prestimulus EMG. Contralateral potentials increased significantly with contraction of the trapezius ipsilateral to the stimulus compared with contraction of the muscle in which they were recorded and decreased significantly with increasing distance from the ipsilateral side. Conclusions: We found ipsilateral and contralateral responses consistent with previous findings. However, we conclude that the contralateral response in trapezius is not a crossed reflex. Muscle Nerve49:362–369, 2014